Frequent Mismatch Repair Protein Deficiency in Mixed Endometrioid and Clear Cell Carcinoma of the Endometrium. (November 2017) - Köbel, Martin; Tessier-Cloutier, Basile; Leo, Joyce; Hoang, Lien N.; Gilks, C. Blake; Soslow, Robert A.; Delair, Deborah; Stewart, Colin J.R.; Lee, Cheng-Han
Abstract : Mixed endometrioid and clear cell carcinoma of the endometrium refers to a scenario in which the tumor exhibits histologic features of both endometrioid and clear cell carcinoma. We observed a tendency for these tumors to occur in a mismatch repair (MMR) protein-deficient molecular background in a prior study that examined a small cohort of mixed-type endometrial carcinomas. The aim of this study was to determine the rate of MMR protein deficiency in a larger series of endometrial mixed endometrioid and clear cell carcinomas, through a retrospective survey of MLH1, PMS2, MSH2, and MSH6 expression in such tumors at 5 tertiary centers. A total of 41 cases were identified and 27 (66%) tumors demonstrated MMR protein deficiency with a comparable frequency across the contributing centers (ranging from 56% to 83%). Among the MMR protein-deficient cases, 59% showed concurrent MLH1 and PMS2 loss, 33% showed concurrent MSH2 and MSH6 loss, and 4% showed isolated PMS2 or MSH6 loss. Compared with a previously published series of 15 pure endometrial clear cell carcinomas, mixed endometrioid and clear cell carcinomas are associated with significantly better disease-specific survival ( P =0.02). In summary, endometrial carcinomas with mixed endometrioid and clear cell histology are frequently MMR protein deficient. This finding has implications both for our understanding of its tumor biology and for the identification of patients with potential Lynch syndrome.